ANALISIS PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENCURIAN DATA PRIBADI DI INDONESIA - Azhari, Sultan Fathan; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Thee developmente of informatione technologye in ethee digital eeraee hase brought significant impacts on people'se lives, e one of which is the increasing risk of personal data theft. This research aims to analyze the effectiveness of law enforcement against perpetrators of personal data theft in Indonesia using the Lawrence M. Friedman legal system theory approach, specifically focusing on the element of legal substance. This studye usese ae normativee juridical researche typee and ise descriptivee in nature. Secondarye datae ise analyzede qualitatively. Conclusions are drawn using deductive logic. The research results indicate that despite the availability of relatively complete legal instruments, there are still various obstacles in their implementation, including unclear legal norms, weak criminal sanctions, the unavailability of supporting technical regulations, and a lack of comprehensive integration among regulations governing personal data protection. Through an analysis of several actual cases, it was found that there is disparity in the imposition of sanctions and the legale systeme has enot ebeene optimal in providing a deterrent effect for perpetrators. Therefore, reformulation of legal substance and harmonization of regulations are necessary to address the challengese of personale datae protectione in thee digital era comprehensively and effectively Keywords: Law Enforcement , Personal Data Protection , Legal System